Data for: Climate change increases evaporative and crop irrigation demand in North America - Emily Williams (22284526) (2025)
Across North America, warmer temperatures have increased reference evapotranspiration (ETo), taxing water resources. This problem is especially pronounced for semi-arid regions with large amounts of irrigated agriculture, such as California’s Central Valley. In this region, increased ETo has increased irrigation demand, but the role of anthropogenic climate change (ACC) in driving this increase has not yet been quantified. Here, we quantify the first-order influence of ACC on ETo and how these changes have translated into increased irrigation demand. We calculated observed and counterfactual ETo over North America using ERA5-Land data and 20 models from the Coupled Model Intercomparison Project Phase 6 (CMIP6). At the scale of North America, we found that ACC accounted for all of the observed ETo increase (1.06 mm/yr) during 1980-2022. The largest observed increases in ETo were found in the southwestern and central regions, where ACC has likely exacerbated trends linked to natural climate variability. The largest ACC contributor to increased ETo was increased vapor pressure deficit, while decreased solar radiation has tempered increased ETo. We estimated that the first-order influence of ACC on agricultural irrigation demands in the Central Valley was equivalent to ~11% of the region’s groundwater loss during this time. Our findings suggest that ACC is accelerating demand for water in this already water-limited region.